Association of temporomandibular disorders and tinnitus with health‐related quality of life: A cross‐sectional study using the Fifth Korea National Health and Nutrition Examination Survey. (13th December 2021) - Kong, Geon‐Sik; Lee, Sook‐Hyun; Park, Kyoung Sun; Cho, Jae‐Heung; Kim, Koh‐Woon; Ha, In‐Hyuk
Abstract: Background: Few studies have examined the associations of temporomandibular disorders (TMDs) and tinnitus with health‐related quality of life on a national level. Objective: We aimed to investigate the associations of TMDs, tinnitus and quality of life among the Korean population, aged 19 years or older. Methods: Data were obtained from the fifth Korea National Health and Nutrition Examination Survey (2012; N  = 5786). TMDs, tinnitus and health‐related quality of life were assessed using self‐report data from EuroQol‐5 Dimension. Participants were divided into four groups: no TMD and no tinnitus, TMD present but no tinnitus, no TMD but tinnitus present and both TMD and tinnitus present. Results: Among the participants, 21.88% had TMD, 24.93% had tinnitus, and 7.74% had both. The prevalence of most TMD and all types of tinnitus was higher among females than among males. The group with both TMD and tinnitus reported the highest percentage of problems in the usual activity, pain/discomfort and anxiety/depression dimensions. Moreover, the odds ratio (OR) for lower quality of life was significantly higher in the group with both TMD and tinnitus compared to the group without TMD and tinnitus: mobility (OR = 1.527, 95% confidence interval [CI]: 1.014–2.300), pain/discomfort (OR = 2.072, 95% CI: 1.570–2.735), anxiety/depression (OR = 1.692, 95% CI: 1.034–2.767), EQ‐5D score (OR = 1.651, 95% CI: 1.121–2.431) and EQ‐VAS (OR = 1.682, 95% CI: 1.246–2.269). Conclusion: The presence of both TMD and tinnitus has a considerable impact on HRQoL in the Korean population. In our study, the group with both TMD and tinnitus showed lower HRQoL than without TMD and tinnitus group. These results emphasise the need for a multilateral and comprehensive approach to address these disorders and provide baseline data for developing appropriate interventions. Abstract : The prevalence of affected HRQoL was the highest in both the TMD and tinnitus present group for the usual activity, pain/discomfort and anxiety/depression dimensions of EQ‐5D. After adjusting for the confounding variables, the group with both TMD and tinnitus showed lower HRQoL than without TMD and tinnitus group.